Pengaruh Variasi Radius Sudu Turbin Angin Darrieus Tipe Sudu-J - Sulistyono Sulistyono; Elka Faizal; Alfi Tranggono Agus Salim (Polinema Press, Politeknik Negeri Malang, 2020)
Utilization of alternative energy, therefore this wind turbine is used as an alternative energy power plant. So this experimental study is used to determine how much influence on the performance of the Darrieus type J-blade vertical shaft wind turbine by varying the blade radius. The method used is a true experimental research method. The independent variables in this study are variations in wind speed of 3, 4, 5, 6, and 7 m / s. The dependent variable in this research is shaft power and efficiency. Then the controlled variables in this study were the number of blades 3 and the front radius of the blade: 5, 10, and 15 mm. The test results and data processing shows that the blade radius of the Darrieus J-blade type of wind turbine affects the performance of the Darrieus J-blade type wind turbine. In testing the highest value was achieved at a blade radius of 15 mm with a wind speed of 7 m / s, namely the shaft power value of 0.323 Watt and the efficiency value of 4.673%.